2021
DOI: 10.1177/03000605211002381
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum visfatin levels and psoriasis and their correlation with disease severity: a meta-analysis

Abstract: Objective To determine the association between serum visfatin levels and psoriasis and to evaluate the correlation between serum visfatin levels and the severity of psoriasis. Methods The electronic databases PubMed®, Embase® and the Cochrane Library were searched for articles published from inception to 1 May 2020. Data were extracted and then standard mean differences (SMDs) and 95% confidence intervals (CIs) were calculated for pooled estimates. Results A total of 11 studies met the inclusion criteria and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
(143 reference statements)
1
3
0
Order By: Relevance
“…A similar trend has been observed for other adipokines in psoriasis, with an increase in those with proinflammatory effects, including resistin [ 188 , 190 ], chemerin [ 191 ], and visfatin [ 192 ], and a decrease in those with anti-inflammatory effects, such as omentin [ 182 , 183 ]. Even more significantly, healing of psoriasis following effective therapy results in the normalization of the aberrant levels of these molecules [ 185 , 191 ].…”
Section: Higher Prevalence Of Traditional CV Risk Factors In Psoriasi...supporting
confidence: 70%
“…A similar trend has been observed for other adipokines in psoriasis, with an increase in those with proinflammatory effects, including resistin [ 188 , 190 ], chemerin [ 191 ], and visfatin [ 192 ], and a decrease in those with anti-inflammatory effects, such as omentin [ 182 , 183 ]. Even more significantly, healing of psoriasis following effective therapy results in the normalization of the aberrant levels of these molecules [ 185 , 191 ].…”
Section: Higher Prevalence Of Traditional CV Risk Factors In Psoriasi...supporting
confidence: 70%
“…In addition, visfatin plays a regulatory role in cell proliferation and apoptosis [ 169 ]. A study by Zou and colleagues determined the associations between serum visfatin levels and psoriasis [ 170 ]. This meta-analysis showed that patients with psoriasis had significantly higher levels of visfatin than controls.…”
Section: Other Adipokines and Their Role In Psoriasismentioning
confidence: 99%
“…A meta-analysis including 11 studies demonstrated that psoriasis patients had higher levels of visfatin (SMD, 0.90; 95% CI, 0.52-1.28), which was associated with ethnicity, PASI, and BMI (34). Visceral fat was associated with psoriasis, hypertriglyceridemia, low high-density lipoprotein, and type 2 diabetes, and these associations were linked to serum IL-6, adiponectin, tumor necrosis factor, and insulin resistance (52).…”
Section: Lipid Metabolismmentioning
confidence: 99%